Analisis Metode K-Medoids Cluster Dalam Mengelompokkan Siswa Yang Berprestasi - Indri Fatma; Heru Satria Tambunan; Fitri Rizki (PDSI, 2022)
Cluster analysis of outstanding students using data mining, namely the K-Medoid Cluster Algorithm. Previously, the school still used the manual method in determining students who excel at the school, so it took a long time and the results were not accurate. K-Medoid Cluster is one of the algorithms used for data classification or grouping, the authors apply the K-Medoid Cluster algorithm in grouping students with high achievement in order to get more accurate, fast, and effective results.